Productivity Enhancement in Blackgram (Vigna mungo L.) through Improved Crop Management Practices on Farmers’ Field (Indian Journal of Extension Education, 2021)
Urd bean (Vigna mungo L.) or black gram is one of the important pulse crop cultivated over 1000 ha area in Erode district of Tamil Nadu. Attempts were made to reduce the yield gap of black gram by adopting integrated crop management practices through cluster frontline demonstrations during 2016-2020 in 250 farmers’ field. The integrated crop management practices comprised of high yielding black gram variety, seed treatment with rhizobium, foliar application of micronutrients, integrated plant protection measures were demonstrated. The results showed that number of pods and seeds per plant were increased by 7.66 and 10.54 per cent respectively over farmers practice. Similarly the average higher grain yield of 7.68 quintal/ha recorded in demonstration plots compared to 6.51 quintal/ha in farmers practice with a yield advantage of 17.99 per cent over the farmer practices. The average extension gap, technology gap and technology index were 1.17 quintal/ha, 0.83 quintal/ha, and 9.75 per cent respectively. About 71.6 per cent farmers were satisfied with the improved crop production technologies. Considering the above facts, Frontline demonstrations were carried out in a systematic and scientific manner on farmer’s field to show the worth of improved production management technologies in black gram for further adoption.